Pengaruh Penggunaan Influencer Marketing terhadap Perilaku Pembelian Konsumen - Annisa Annisa; Nabila Al Falisa (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study examines the impact of influencer marketing on consumer purchasing behaviour in the rapidly evolving digital marketplace. Using a quantitative method, the study was conducted through surveys of social media users exposed to influencer content. Several key dimensions of influencer marketing were evaluated, including trust in influencers, content relevance, and audience engagement. The results indicate that influencer marketing substantially impacts brand awareness, purchase intention and actual purchase decisions. These study provide companies with insights to help them optimise their digital marketing strategies by collaborating with the right influencers.